An NHC-CuCl functionalized metal–organic framework for catalyzing β-boration of α, β-unsaturated carbonyl compounds. Issue 16 (28th March 2019) - Yao, Qingxia; Lu, Xiufang; Liu, Kaili; Ma, Chao; Su, Jie; Lin, Cong; Li, Dacheng; Dou, Jianmin; Sun, Junliang; Duan, Wenzeng
Abstract : A microporous MOF functionalized with in situ generated NHC-Cu(i )Cl units (1 ), which can catalyze β-boration of α, β-unsaturated carbonyl compounds, has been synthesized. Abstract : A microporous metal–organic framework functionalized with in situ generated NHC-CuCl units (1 ) has been successfully synthesized from a novel imidazolium-containing ligand. In particular, the MOF1 can catalyze β-boration of α, β-unsaturated carbonyl compounds, while the isoreticular version of1 (1-im ) modified with only imidazolium moiety cannot. This work demonstrates for the first time the heterogeneous catalysis of NHC-Cu(i )Cl within a MOF solid.